Hubungan Pengetahuan Dengan Kepatuhan Pengobatan Antiretroviral (ARV) Pada Ibu Hamil Dengan Human Immunodeficiency Virus (HIV) / Acquired Immuno Deficiency Syndrome (AIDS) - Kadek Ari Dwi Lestari; Ni Ketut Somoyani; I Gusti Ayu Surati (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2018)
Antiretroviral (ARV) treatment in pregnant women with HIV can reduce the risk of mother-to-child HIV transmission. The purpose of this study was to identify the association of knowledge with antiretroviral treatment adherence in pregnant women with HIV / Acquired Immuno Deficiency Syndrome (AIDS) at Sanglah Hospital and Wangaya Hospital in May - June 2018. The design of this study was analytic correlation with cross-sectional approach. Samples in this study were all pregnant women with HIV / AIDS who underwent antiretroviral (ARV) treatment in Denpasar City in 2018 that met the inclusion criteria of 40 people. Sampling technique in this research is non probability sampling with consecutive sampling method. Research data were obtained by using questionnaire. Data analysis was done gradually including univariate analysis and bivariate analysis by using contingency coefficient test. The results of statistical tests conducted obtained p-value of 0.027. Conclusion from this research there is correlation between knowledge with antiretroviral treatment adherence in pregnant woman with HIV / Acquired Immuno Deficiency Syndrome (AIDS) in Denpasar City 2018. Health worker in PMTCT should be provide counseling especially about ARV treatment in pregnancy to improve patient's medication adherence